The Phillips Curve and NAIRU Revisited: New Estimates for Germany - Bernd Fitzenberger; Wolfgang Franz; Oliver Bode (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2007)
This paper provides new estimates of a time?varying NAIRU for Germany taking account of the structural break caused by German unification based on the Kalman Filter and on a partially linear model as two alternatives. Estimating a standard Phillips curve, the sum of coefficients associated with expected inflation is far beyond unity, whatever measure of expected inflation rates is employed. Therefore, either the NAIRU concept is not applicable to Germany or, as it is our suggestion, one estimates the unemployment rate that is compatible with a tolerable inflation rate of say 2 percent following roughly the inflation target put forward by the European Central Bank. The estimates presented in this paper suggest that the NAIRU compatible with 2 percent inflation in Germany is currently around 7 percent if the definition of unemployment follows the concept of the ILO. In contrast to the consensus in the literature, our estimates suggest furthermore that the NAIRU in Germany has not increased since the early 1990?s.
Keywords: C22; E31; E24; 330; NAIRU; unemployment; inflation; Phillips curve; Okun?s Law; German unification; Kalman Filter; partially linear model; Phillips-Kurve; Natürliche Arbeitslosigkeit; Schätzung; Deutschland